Green Supply Chain Management Enhances Competitiveness and Accelerates Economic Growth in India’s Agro-Food Sector (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study argues that green supply chain management (GSCM) significantly boosts competitiveness and economic growth in India's agro-food sector. It analyzes how Indian agro-food companies adopt GSCM practices. As a part of the GSCM approach, eco-friendly packaging, reverse logistics, and energy-efficient transportation are considered to maintain their product quality. Apart from the GSCM approach, there is the impact these practices have on the competitiveness and financial performance of the rest of the mode of production. In this study, quantitative methods and secondary data from government and industry sources are used. The research demonstrates how these GSCM elements strengthen company performance and contribute to the agro industry’s sectoral growth. Using descriptive statistics and core hypotheses, the study identifies prevalent practices in the agro-industry. Through this study, we review relevant policy frameworks, identify the obstacles in this sector, and recommend strategies for broader GSCM adoption. The investigation further connects green logistics, sustainable sourcing of agro-green products, and identifies emerging technologies for operational cost reductions and market expansion. The expected outcome of this study is that technological advancements, such as hybrid seeds and modern irrigation, will drive higher productivity and economic growth in Indian agriculture. Practical recommendations are provided to help policymakers, industry leaders, and academics build effective, sustainable, and competitive green agri-food supply chains in India.